ACUTE EFFECTS OF DYNAMIC STRETCHING EXERCISE ON POWER OUTPUT DURING CONCENTRIC DYNAMIC CONSTANT EXTERNAL RESISTANCE LEG EXTENSION - YAMAGUCHI, TAICHI; ISHII, KOJIRO; YAMANAKA, MASANORI; YASUDA, KAZUNORI (Journal of strength and conditioning research, 2007)
The purpose of the present study was to clarify the acute effect of dynamic stretching exercise on muscular performance during concentric dynamic constant external resistance (DCER, formally called isotonic) muscle actions under various loads. Concentric DCER leg extension power outputs were measured in 12 healthy male students after 2 types of pretreatment. The pre- treatments were(a) dynamic stretching treatment including 2 types of dynamic stretching exercises of leg extensors and the other 2 types of dynamic stretching exercises simulating the leg extension motion (2 sets of 15 times each with 30-second rest periods between sets; total durationabout 8 minutes), and (b) nonstretching treatment by resting for 8 minutes in a sitting position. Loads during measurement of the power output were set to 5, 30, and 60% of the maximum voluntary contractile (MVC) torque with isometric leg extension in each subject. The power output after the dynamic stretching treatment was significantly (p < 0.05) greater than that after the nonstretching treatment under each load (5% MVC468.4 ± 102.6 W vs. 430.1 ± 73.0 W; 30% MVC520.4 ± 108.5 W vs. 491.0 ± 93.0 W; 60% MVC487.1 ± 100.6 W vs. 450.8 ± 83.7 W). The present study demonstrated that dynamic stretching routines, such as dynamic stretching exercise of target muscle groups and dynamic stretching exercise simulating the actual motion pattern, significantly improve power output with concentric DCER muscle actions under various loads. These results suggested that dynamic stretching routines in warm-up protocols enhance power performance because common power activities are carried out by DCER muscle actions under various loads.